Effect of planting densities on productivity of different cultivars in apple (Malus × domestica) - MIR, JI; AHMED, N; SINGH, D B; SHARMA, O C; SHARMA, A; SHAFI, WAJIDA; ZAFFER, SHAFIA; HAMID, ASMA (The Indian Journal of Agricultural Sciences, 2016)
Relationship between crop density and yield efficiency was studied to assess the influence of fruit number on yield of cultivars under different planting densities in apple (Malus × domestica Borkh). Under 4.0 × 4.0 m spacing, crop density ranged between 0.38 in cv Red Fuji to 2.11 in American Apirogue with an average of 1.20 and under 2.5 × 2.5 m spacing, crop density ranged from 0.44 in cv Red Fuji to 1.69 in Vance Delicious with an average of 1.22. Maximum fruit weight (197 g) was observed in cv Red Delicious and minimum fruit weight (120 g) was observed in American Apirogue under 4.0 × 4.0 m. Yield efficiency under 4.0 × 4.0 m spacing ranged from 0.06 kg/cm2 for Red Fuji to 0.31 kg/cm2 for Red Delicious with an average of 0.19 kg/cm2. Maximum yield efficiency (0.28 kg/cm2) was observed in cv Mollies Delicious and Vance Delicious but minimum (0.07 kg/cm2) in Red Fuji under 2.5 × 2.5 m spacing. Thus crop load influences both fruit size and yield efficiency of apple varieties differently under two densities.